Factors related to health literacy among Brazilian adolescents: cross-sectional study - Pimentel, Sidiany Mendes; Avila, Marla Andreia Garcia de [UNESP]; Medeiros, Vinnicius Dias Alves de; Prata, Rafaela Aparecida [UNESP]; Nunes, Rubens de Carvalho [UNESP]; Silva, Juliana Bastoni da (Univ Sao Paolo, 2024)
Objective: To analyze the relationship between sociodemographic and clinical factors with health literacy in Brazilian adolescents. Method: This is a cross-sectional study with 526 adolescents aged 14 to 19. Data were collected virtually between July and September 2021 using a sociodemographic characterization questionnaire, clinical profile and the Health Literacy Assessment Tool - Portuguese version. The variables were evaluated by multiple linear regression with normal response, with significance p < 0.05. Results: The average age was 16.9 years (+/- 1.6), the average health literacy score was 25.3 (+/- 5.4). Female gender (p = 0.014), university educational level (p = 0.002) and use of medication (p = 0.020) were related to higher levels of health literacy. Adolescents with chronic illnesses had a higher total literacy score, on average 1.51 points, compared to those without chronic illnesses. Conclusion: Male adolescents and those with less education performed worse in health literacy and, therefore, deserve special attention in health promotion actions.
Keywords: Adolescent Health; Health Literacy; Health promotion; Social Determinants of Health; Adolescent Development